MYC at the tumor–immune interface: mechanisms of immune escape and immunotherapy resistance - González-Larreategui, Íñigo; Valdés-Bango Martín, Manrique; Casacuberta-Serra, Sílvia; Soucek, Laura (Frontiers in Immunology, 2026)
Immunotherapies have transformed cancer treatment by harnessing the immune system to recognize and eliminate malignant cells, offering durable clinical benefit across diverse tumor types. Despite successes with immune checkpoint inhibitors (ICIs) and other strategies like cytokines, oncolytic viruses, cancer vaccines, bispecific antibodies, and adoptive cell therapies, substantial fractions of patients still fail to respond or develop resistance. The oncogene MYC, deregulated in ~70% of human cancers, has emerged as a central driver of immune evasion and a key contributor to immunotherapy failure. MYC regulates broad transcriptional networks controlling proliferation, metabolism, angiogenesis, and cell survival, while also orchestrating profound remodeling of the tumor microenvironment (TME). Mechanistically, oncogenic MYC suppresses antigen processing and presentation, attenuates interferon signaling, and upregulates immune checkpoints such as PD-L1 and CD47. Concurrently, MYC stimulates secretion of immunosuppressive cytokines and chemokines that recruit regulatory T cells, myeloid-derived suppressor cells, and M2 macrophages, while driving metabolic reprogramming that fosters nutrient competition, hypoxia, and acidosis, impairing effector T- and NK-cell function. Through these pathways, MYC promotes primary, adaptive, and acquired resistance to immunotherapy. Targeting MYC, directly or indirectly, holds promise to restore immune surveillance and potentiate immunotherapeutic efficacy. This review highlights MYC as a master regulator of tumor–immune interactions and underscores the therapeutic potential of MYC inhibition to overcome resistance and expand the clinical impact of cancer immunotherapy.